Ethnic Chinese during the New Order: Teaching Materials Development for History Learning based on Multiculturalism (History Department, Semarang State University and Historian Society of Indonesia, 2020)
The history of Indonesian Chinese society is still rarely studied in history learning at school. One of them concerns the discriminatory treatment of them during the New Order era. This article aimed to describe discriminatory policies against ethnic Chinese during the New Order era, to present it as a history teaching materials, and to elaborate on the importance of studying it for the younger people. This research used historical and qualitative descriptive method using literature. The result showed that (1) Ethnic Chinese in the New Order era received discriminatory treatment in various sectors. It was a violation of human rights and susceptible to trigger conflict. (2) The study of the Chinese people can be served as a history teaching material in the subject of the New Order era. (3) Teaching materials development is expected to be used to create awareness of multiculturalism through history teaching.Sejarah masyarakat Tionghoa Indonesia masih jarang dikaji dalam pembelajaran sejarah di sekolah. Salah satunya mengenai perlakuan diskriminatif terhadap mereka pada masa Orde Baru. Maka penelitian ini bertujuan untuk mendeskripsikan kebijakan diskriminatif terhadap etnis Tionghoa selama Orde Baru, menyajikannya sebagai bahan ajar sejarah, dan menguraikan arti penting mempelajarinya bagi generasi muda. Penelitian ini menggunakan metode historis dan kualitatif deskriptif dengan studi pustaka. Hasil penelitian menunjukkan bahwa (1) Etnis Tionghoa pada masa Orde Baru menerima perlakuan diskriminatif di berbagai sektor. Hal itu merupakan pelanggaran atas hak asasi manusia dan terbukti rentan konflik. (2) Studi tentang dinamika masyarakat Tionghoa tersebut dapat disajikan sebagai bahan ajar sejarah pada pokok bahasan masa Orde Baru. (3) Kajian tersebut diharapkan dapat menciptakan kesadaran multikulturalisme melalui pembelajaran sejarah.